Website Design Of Junior High School (Smp) Negeri 21 Bengkulu As Information Media And Promotion - Yusril Mahendra; Kirman Kirman; RG Guntur Alam; Marissa Utami (Jurnal Komputer, Informasi dan Teknologi, 2023)
In cyberspace there is a lot of information that is needed, especially in the world of education, therefore in this Global network SMP Negeri 21 Bengkulu Tengah which is one of the educational institutions in Bengkulu Province, especially in Central Bengkulu, needs to make breakthroughs and innovations in promoting its existence by creating a web site. With the creation of a Web site SMP Negeri 21 Bengkulu Tengah is very helpful for students and teachers in getting the information they need, all information needs about activities in the teaching and learning process and extracurricular activities can be obtained and seen on this website. The information is presented in a series of systems in the form of attractive web pages and designs using Xampp, Mysql and Dreamweaver Cs4 programs.The process of running the program to enter the website page the first time a person will enter on the initial display there are several menu tobols. The profile page is information at a glance about the school and activities at the school while our Services page has several menus including menus of school facilities, study rooms, school buildings, and sports, then on the contact us page there is complete school address information. The next menu is the guest book, in this guest book there is a column that can be filled in by web site visitors in the form of suggestions and responses that are to advance the Website of SMP Negeri 21 Bengkulu Tengah. The next menu is an information menu containing a location plan and road direction, this aims to provide information to website visitors in order to find out the location plan of SMP Negeri 21 Bengkulu. From the information above, it can be concluded that website programming using Dreamweaver CS4 macromedia can produce a website that looks attractive, and helps provide information and as a means of promotion increases competitiveness in accepting new students, and this website can be updated.